Differentially Methylated DNA Regions in Monozygotic Twin Pairs Discordant for Rheumatoid Arthritis: An Epigenome-Wide Study - Svendsen, Anders J.; Gervin, Kristina; Lyle, Robert; Christiansen, Lene; Kyvik, Kirsten; Junker, Peter; Nielsen, Christian; Houen, Gunnar; Tan, Qihua (Frontiers in Immunology, 2016)
Objectives: In an explorative epigenome-wide association study (EWAS) to search for gene independent, differentially methylated DNA positions (DMPs) and regions (DMRs) associated with rheumatoid arthritis (RA) by studying monozygotic (MZ) twin pairs discordant for rheumatoid arthritis. Methods: Genomic DNA was isolated from whole blood samples from 28 monozygotic (MZ) twin pairs discordant for RA. DNA methylation was measured using the HumanMethylation450 BeadChips. Smoking, anti-cyclic citrullinated peptide antibodies and immunosuppressive treatment were included as covariates. Pathway analysis was performed using GREAT. Results: Smoking was significantly associated with hypomethylation of a DMR overlapping the promoter region of the RNF5 and the AGPAT1, which are implicated in inflammation and autoimmunity, whereas DMARD treatment induced hypermethylation of the same region. Additionally, the promotor region of both S100A6 and EFCAB4B were hypomethylated and both genes have previously been associated with RA. We replicated several candidate genes identified in a previous EWAS in treatment naïve RA singletons. Gene set analysis indicated the involvement of immunologic signatures and cancer-related pathways in RA. Conclusion: We identified several differentially methylated regions associated with RA which may represent environmental effects or consequences of the disease and plausible biological pathways pertinent to the pathogenesis of rheumatoid arthritis